Overlapping Block Transform: Window Design, Fast Algorithm and an Image Coding Experiment - Edler, Bernd; Temerinac, Miodrag (IEEE Transactions on Communications, 1995)
A window design and fast algorithm for the overlapping block transform (OBT) of size N/spl times/L are presented. The presented algorithm for the OBT reduces the calculation complexity to an N/spl times/N transform with a fast algorithm and a simple preprocessing including windowing. A signal-independent window optimization strategy is introduced for image coding application. Results for a first-order Markov model and an image coding experiment show, that the coding gains of the optimized OBTs increase and blocking effects decrease with increasing window length L. A comparison with DCT-coding shows that the OBT, which has a slightly increased realization complexity, provides higher coding gain and a significant blocking effect reduction.<br